Magnetic microstructure and magnetoresistive effect in Corbino’s disk with magnetic ordering - Halauchuk, Victoryia I.; Lukashevich, Michail G. (Journal of the Belarusian State University. Physics, 2019)
The atomic- and magnetic-force microscopy results are presented for the transverse magnetoresistive effect in Corbino’s disk with magnetic ordering. The disk was prepared on the setall substrate from permalloy film by means of ion-beam sputtering. It is shown that, independently of the magnetic field-disk plane orientation, magnetoresistance is negative and it reveals a sharp peak for a weak magnetic field in the interval В = 0.2-8.0 mT due to the domain wall motion. A position of the peak, its amplitude and half-width depends significantly on the magnetic field orientation with respect to the disk plane. During the out-of-plane magnetic field measurements changing of a sign of magnetoresistance within the peak and also changes in a slope of magnetoresistance due to the Lorentzian positive magnetoresistance contribution were observed.
Keywords: permalloy; substrate; film; roughness; magnetic microstructure; Corbino disk; magnetoresistance